Porous graphene-based double transition metal selenide heterojunction composite material as well as preparation method and application thereof

By constructing a metal selenide heterojunction structure on a porous graphene matrix, the problem of insufficient conductivity and structural stability of the negative electrode material of sodium ion battery is solved, and high capacity and cyclic stability are improved, suitable for high-performance sodium ions Preparation of batteries.

CN119495723APending Publication Date: 2025-02-21武汉启钠新能源科技有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411368645.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials have low conductivity, and irreversible volume changes are easily generated during sodium ion sodium-embedded/desodium desodium, resulting in low actual capacity and poor cycle stability, limiting its large-scale energy storage technology. Application in.

Method used

Using porous graphene-based bitransition metal selenide heterojunction composite material, a metal selenide heterojunction structure is constructed on a porous graphene matrix, providing a trans-layer transportation pathway of sodium ions to improve ion conductivity and structural stability.

Benefits of technology

It significantly improves the theoretical capacity and cyclic stability of the negative electrode material of sodium ion battery, enhances the rate performance and electrochemical stability, and is suitable for the preparation of high-performance sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a porous graphene-based double transition metal selenide heterojunction composite material. The composite material comprises a porous graphene matrix and Ni0.85Se / CoSe polygonal nanoparticles loaded on the surface of the porous graphene matrix. According to the invention, a metal selenide heterojunction structure is constructed on a porous graphene matrix, so that a sodium ion cross-layer transport path can be effectively provided, and the graphene-based metal selenide heterojunction composite material has high ionic conductivity, small volume change in a working process, high reversible capacity and excellent rate and cycle performance; when the composite material is used as the negative electrode of the sodium ion battery, the selenide heterojunction structure close to the graphene hole can effectively reduce the structure and volume change, shorten the ion transmission distance, and effectively enhance the electrochemical stability and improve the capacity in the charging and discharging process; the sodium ion energy storage requirements of high specific capacity, long service life and safety can be met, and the method is suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy materials, and in particular relates to a porous graphene-based double transition metal selenide heterojunction composite material and a preparation method and application thereof. Background Art

[0002] At present, the global energy demand has surged. As a non-clean energy source, the large-scale use of fossil fuels has caused increasingly serious environmental problems. More and more investment has been made in the research of new energy sources, such as solar energy, geothermal energy, wind energy, ocean energy, biomass energy and nuclear fusion energy. In new renewable energy storage systems, high-capacity lithium-ion batteries have been widely studied and applied. Sodium, which is in the same main group as lithium, is abundant and cheap, which has triggered the research on sodium-ion batteries. Sodium has similar properties to lithium and is environmentally friendly, so sodium-ion batteries have broad application prospects and huge potential.

[0003] Since sodium ions have a larger ionic radius, the insertion and extraction of sodium during operation will have a negative impact, thus affecting the electrochemical performance. At present, the research focus of sodium ion negative electrode materials is on capacity and service life. Nowadays, negative electrode materials such as transition metal oxides, sulfides, selenides and tellurides are beginning to be used in sodium-ion batteries. The metal-selenium ionic bond is weak, so the sodium insertion / de-sodiumization process of transition metal selenides is faster. However, metal selenides are not very conductive and are prone to irreversible volume changes during the sodium ion insertion / de-sodiumization process. This results in the actual capacity of transition metal selenides being not high, and the irreversible volume change reduces the cycle stability of the battery, thereby affecting the practical application of selenides in large-scale energy storage technology.

[0004] Graphene has attracted a lot of research due to its excellent conductivity and electrochemical properties. As a two-dimensional nanomaterial, graphene can efficiently transport ions in a plane. Loading transition metal selenides on graphene can effectively improve conductivity. Graphene-transition metal selenide composite materials combine the advantages of transition metal selenides and graphene, thereby improving capacity. However, the cross-layer transport of ions between graphene sheets is very difficult and the general transition metal selenides have insufficient ion transport capacity and structural stability, which reduces their theoretical capacity and limits their application and development. The patent "CN116525794A Preparation method and application of porous graphene-loaded selenium-cobalt-iron nanoparticle composite material" discloses a method for loading FeCo 2 Se 4The porous graphene material with a porous structure and the graphene-transition metal selenide composite material have improved the ion cross-layer transmission ability, but its structural stability has not been significantly improved, and the problem of low conductivity of the transition metal selenide itself has not been solved. The patent "CN116387481A Preparation method and application of a heterogeneous structure egg yolk shell type double transition metal selenide composite material" uses a tight bimetallic heterojunction to improve the charge transfer ability and structural stability of the metal selenide itself, but the formation of a heterojunction by coating a metal-organic framework with a metal hydroxide is too cumbersome, and the overall capacity improvement effect of the resulting composite material is limited. Summary of the invention

[0005] The main purpose of the present invention is to provide a porous graphene-based double transition metal selenide heterojunction composite material in view of the problems and shortcomings of the prior art. The composite material can effectively provide a cross-layer transport pathway for sodium ions by constructing a metal selenide heterojunction structure on a porous graphene substrate. The composite material has high ionic conductivity, small volume change during the working process, high reversible capacity, and excellent rate and cycle performance. The composite material is used as the negative electrode of a sodium ion battery. The selenide heterojunction structure close to the graphene pores can effectively reduce structural and volume changes, shorten the ion transmission distance, and effectively enhance the electrochemical stability and improve the capacity during the charge and discharge process, thereby providing a new idea for the preparation of high-performance sodium ion batteries.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A porous graphene-based double transition metal selenide heterojunction composite material, comprising a porous graphene matrix and Ni loaded on the surface thereof 0.85 Se / CoSe polygonal nanoparticles.

[0008] Furthermore, the pore size of the porous graphene matrix is ​​50 to 100 nm.

[0009] Furthermore, the Ni 0.85 The particle size of Se / CoSe polygonal nanoparticles is 100-200 nm.

[0010] The present invention also provides a method for preparing the above-mentioned porous graphene-based double transition metal selenide heterojunction composite material, comprising the following steps:

[0011] S1. Dissolve a cobalt source and a nickel source in water to obtain a metal salt solution; subject the graphene source solution to ultrasound to obtain a graphene solution; drop the metal salt solution into the graphene solution, stir, add ammonia water, oil bath, and freeze-dry to obtain a metal-graphene precursor;

[0012] S2, calcining the obtained metal-graphene precursor to obtain metal-graphene;

[0013] S3. Selenizing the obtained metal-graphene with a selenium source to obtain the porous graphene-based double transition metal selenide heterojunction composite material (NCS / HG).

[0014] In the above scheme, the molar ratio of the cobalt source to the nickel source is 1 to 2:3.

[0015] In the above scheme, the cobalt source can be at least one of cobalt acetate, cobalt nitrate, etc.; the nickel source can be at least one of nickel acetate, nickel nitrate, etc.

[0016] In the above scheme, the graphene source is at least one of graphene oxide, hydrogenated graphene, fluorinated graphene, etc.

[0017] Furthermore, in the graphene source solution, the concentration of the graphene source is 3 to 6 mg / ml.

[0018] In the above scheme, in S1, the mass ratio of the introduced cobalt source to the graphene source is 2:1 to 3.

[0019] In the above scheme, the ultrasonic time of the graphene source solution is 0.5 to 1 hour.

[0020] In the above scheme, the stirring time in S1 is 12 to 24 hours; the oil bath temperature is 60 to 80° C., the time is 4 to 6 hours; and the freeze-drying time is 12 to 24 hours.

[0021] In the above scheme, the concentration of the ammonia water is 30-40wt%.

[0022] Further, the ammonia water (NH introduced 4 + ) and the cobalt source in a molar ratio of 1:95 to 205.

[0023] In the above scheme, the selenium source is selenium powder.

[0024] In the above scheme, in S3, the mass ratio of the introduced selenium source to the metal-graphene is 5 to 3:1.

[0025] In the above scheme, the calcination and selenization equipment is a tubular furnace.

[0026] In the above scheme, the atmosphere used in the calcination and selenization steps is N 2 or Ar.

[0027] In the above scheme, the calcination temperature is 700-900° C. and the time is 1-3 hours.

[0028] In the above scheme, the selenization temperature is 500-700° C. and the time is 1-3 hours.

[0029] Furthermore, the calcination temperature is higher than the selenization temperature.

[0030] In the above scheme, the heating rate adopted in the calcination step is 2 to 6°C / min.

[0031] In the above scheme, the heating rate used in the selenization step is 2 to 6° C. / min.

[0032] The present invention also discloses an electrode sheet slurry prepared by using the porous graphene-based double transition metal selenide heterojunction composite material, which is prepared by mixing the porous graphene-based double transition metal selenide heterojunction composite material with conductive carbon and a binder in a mass ratio of 5 to 8:1 to 3:1.

[0033] Furthermore, the conductive carbon is one or more of acetylene black, Ketjen black, conductive carbon black and the like.

[0034] Furthermore, the binder is polyvinylidene fluoride or carboxymethyl cellulose.

[0035] The electrode sheet slurry is coated, dried and cut to obtain electrode sheets, which are further used in preparing sodium ion batteries.

[0036] Furthermore, the counter electrode used in the sodium ion battery is metallic sodium.

[0037] Furthermore, the electrolyte used in the sodium ion battery is a diethylene glycol methyl ether solution of sodium hexafluorophosphate or a propylene carbonate solution of sodium perchlorate.

[0038] Furthermore, the diaphragm used in the sodium ion battery is one or more of a glass fiber diaphragm, a cellulose diaphragm, and a PVDF diaphragm.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) The porous graphene-based double transition metal selenide heterojunction composite material of the present invention comprises a porous graphene matrix and a Ni 0.85Se / CoSe polygonal nanoparticles; by introducing a double transition metal heterojunction, the metallicity and conductivity of the selenide can be effectively enhanced, and at the same time, the synergistic effect of the heterojunction bimetal and the multi-electron reaction are beneficial to reducing the sodium ion adsorption energy and the barrier of electron conduction, and improving the sodium ion storage capacity, surface adsorption capacity and migration capacity; in addition, the electronic coupling on the constructed selenide heterojunction interface is stronger, which can promote the embedding / ejection process of sodium ions, improve the charge transfer ability and structural stability of the metal selenide itself, and thus effectively improve the rate performance of the resulting composite material; the transition metal selenide heterojunction overcomes the problems of weak ion transmission ability and insufficient structural stability of general transition metal selenides, and can effectively improve its theoretical capacity; in addition, the heterojunction is directly generated during the selenization process, and the process involved is simple.

[0041] (2) The present invention adopts an in-situ growth method to grow Ni 0.85 The Se / CoSe heterojunction is in situ grown on the graphene nanosheet; the holes adjacent to the selenide heterojunction provide a buffer space for the volume change during the charge and discharge process, and can shorten the distance between the selenide and the electrolyte ions, promoting the sodium insertion and de-sodiumization process; in addition, for traditional graphene materials, the ion transport direction is limited to the two-dimensional surface of the graphene, and the porous graphene structure formed by the present invention provides an ion cross-layer transport pathway; the porous graphene structure not only improves the ion transport efficiency, but also increases the structural stability, which is conducive to promoting the effective improvement of the rate performance and cycle stability.

[0042] (3) The composite material of the present invention is used as the negative electrode material of the sodium ion battery. The particularity of its heterojunction structure and the synergistic effect of the double transition metals are utilized to promote the sodium ion diffusion kinetics and electron transfer, and can exhibit excellent rate capacity and cycle performance; the combination of porous graphene and heterojunction is structurally conducive to the insertion and extraction of sodium ions, and the transition metal heterostructure enhances the structural stability, so that the obtained composite material exhibits excellent rate performance and cycle stability, and can achieve high specific capacity, long life, and safe sodium ion energy storage requirements, which is suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is the XRD diagram of the product obtained in Example 1 of the present invention.

[0044] Figure 2 This is a SEM image of the product obtained in Example 1 of the present invention.

[0045] Figure 3 This is the TEM selected area electron diffraction pattern of the product obtained in Example 1 of the present invention.

[0046] Figure 4 This is the SEM image of the product obtained in Comparative Example 3.

[0047] Figure 5 This is the SEM image of the product obtained in Comparative Example 4.

[0048] Figure 6 This is a comparative rate performance diagram of batteries assembled from the products obtained in Example 1 of the present invention and in Comparative Example 1.

[0049] Figure 7 The batteries assembled from the products obtained in Example 1 of the present invention and Comparative Example 1 were respectively -1 The cycle performance diagram below. DETAILED DESCRIPTION

[0050] The technical scheme adopted in the present invention will be clearly and specifically described below by examples and comparative examples, which are only examples of the present invention, do not represent all embodiments, and do not limit the scope of the present invention. The embodiments in the present invention, and those skilled in the art make various changes or modifications according to the present invention, and these equivalent forms also belong to the scope protected by the present invention. Unless otherwise specified, the equipment and reagents used in the present invention are conventional commercial products in the field of the present technology.

[0051] In the following examples, the graphene oxide solutions used were all prepared by the Hummers method, which includes the following steps:

[0052] S1. Disperse 1g of graphite powder in 23ml of concentrated sulfuric acid and stir in an oil bath at 45°C for 24h;

[0053] S2, 0.1NaNO 3 Add S1 to the solution, react for 5 minutes, place in ice water, continue stirring and slowly add 3g KMnO 4 ; After 15 minutes, slowly drip 46 ml of water, place in an oil bath at 95°C for 20 minutes, take out and cool, then drip 10 ml of hydrogen peroxide, and stir for 10 minutes;

[0054] S3, centrifuging the solution obtained in S2, washing with 230 ml of 12% by volume hydrochloric acid solution, and then washing with water until neutral; then dissolving the obtained solid in water, ultrasonically stripping it 6 times, centrifuging and taking the supernatant to obtain the graphene solution, the concentration of which is 4-6 mg / ml, wherein the graphene sheet size is 10-20 μm, and the thickness is 25-40 nm.

[0055] Example 1

[0056] A porous graphene-based double transition metal selenide heterojunction composite material, the preparation method of which comprises the following steps:

[0057] S1, 122.2 mg Co(CH 3 COO 2 ·4H2 O and 224.1mg Ni(CH 3 COO 2 ·4H 2 O was dispersed in deionized water and dropped into 30 ml of a graphene solution with a concentration of 5 mg / ml under stirring; after the mixed solution was stirred continuously for 12 h, ammonia water (0.6 mg, concentration of 30 wt%) was added, and after being placed in an oil bath at 80 ° C for 4 h, freeze-dried to obtain a black solid;

[0058] S2, the black solid obtained in S1 was heated to N 2 Calcinate at 800℃ for 2h, heating rate 5℃ / min;

[0059] S3. The calcined product obtained in S2 and selenium powder (the mass ratio of selenium powder to the calcined product obtained in S2 is 5:1) are calcined at 650°C for 2h with a heating rate of 5°C / min to obtain the graphene-based bimetallic selenide composite material.

[0060] Example 2

[0061] A porous graphene-based double transition metal selenide heterojunction composite material, the preparation method of which comprises the following steps:

[0062] S1, 122.2 mg Co(NO 3 ) 2 6H 2 O and 224.1mg Ni(NO 3 ) 2 6H 2 O was dispersed in deionized water and dropped into 30 ml of a 3 mg / ml graphene solution under stirring; after the mixed solution was stirred continuously for 12 h, ammonia water (0.28 mg, concentration of 30 wt%) was added, and after being placed in an oil bath at 80 ° C for 4 h, freeze-dried to obtain a black solid;

[0063] S2, the black solid obtained in S1 was heated to N 2 Calcinate at 800℃ for 2h, heating rate 5℃ / min;

[0064] S3. The calcined product obtained in S2 and selenium powder (the mass ratio of selenium powder to the calcined product obtained in S2 is 5:1) are calcined at 650°C for 2h with a heating rate of 5°C / min to synthesize a graphene-based metal selenide composite material.

[0065] Comparative Example 1

[0066] A graphene-based bimetallic selenide composite material, the preparation method of which comprises the following steps:

[0067] S1, 122.2 mg Co(CH 3 COO2 ·4H 2 O and 224.1mg Ni(CH 3 COO 2 ·4H 2 O was dispersed in deionized water and dropped into 30 ml of a graphene solution with a concentration of 5 mg / ml under stirring; after the mixed solution was stirred continuously for 12 h, ammonia water (0.6 mg, concentration of 30 wt%) was added, and after being placed in an oil bath at 80 ° C for 4 h, freeze-dried to obtain a black solid;

[0068] S2, the solid 2 The graphene-based bimetallic selenide composite material was synthesized by calcining selenium powder at 650 °C for 2 h.

[0069] Comparative Example 2

[0070] A porous graphene-based double transition metal selenide heterojunction composite material, the preparation method of which comprises the following steps:

[0071] S1, 122.2 mg Co(CH 3 COO 2 ·4H 2 O and 122.2mg Ni(CH 3 COO 2 ·4H 2 O was dispersed in deionized water and dropped into 30 ml of a graphene solution with a concentration of 5 mg / ml under stirring; after the mixed solution was stirred continuously for 12 h, ammonia water (0.28 mg, concentration of 30 wt%) was added, and after being placed in an oil bath at 80 ° C for 4 h, freeze-dried to obtain a black solid;

[0072] S2, the black solid obtained in S1 was heated to N 2 Calcinate at 550℃ for 2h, heating rate 5℃ / min;

[0073] S3. calcining the calcined product obtained in S2 and selenium powder at 500° C. for 2 h with a heating rate of 5° C. / min to obtain the graphene-based bimetallic selenide composite material.

[0074] Comparative Example 3

[0075] A graphene-based bimetallic selenide composite material, the preparation method of which comprises the following steps:

[0076] S1, 122.2 mg Co(CH 3 COO 2 ·4H 2 O and 224.1mg Ni(CH 3 COO 2 ·4H 2O was dispersed in deionized water and dropped into 30 ml of a graphene solution with a concentration of 5 mg / ml under stirring; the mixed solution was continuously stirred at room temperature for 16 h and then freeze-dried to obtain a solid;

[0077] S2, the solid obtained in S1 is heated to N 2 Calcinate at 800℃ for 2h, heating rate 5℃ / min;

[0078] S3. The calcined product obtained in S2 and selenium powder (the mass ratio of selenium powder to the calcined product obtained in S2 is 5:1) are calcined at 650°C for 2h with a heating rate of 5°C / min to obtain the graphene-based bimetallic selenide composite material.

[0079] Comparative Example 4

[0080] A porous graphene-based double transition metal selenide heterojunction composite material, the preparation method of which comprises the following steps:

[0081] S1, 122.2 mg Co(CH 3 COO 2 ·4H 2 O and 224.1mg Ni(CH 3 COO 2 ·4H 2 O was dispersed in deionized water and dropped into 30 ml of a graphene solution with a concentration of 5 mg / ml under stirring; after the mixed solution was stirred continuously for 12 h, ammonia water (0.6 mg, concentration of 30 wt%) was added, and after being placed in an oil bath at 80 ° C for 4 h, freeze-dried to obtain a black solid;

[0082] S2, the black solid obtained in S1 was heated to N 2 Calcinate at 500℃ for 2h, heating rate 5℃ / min;

[0083] S3. The calcined product obtained in S2 and selenium powder (the mass ratio of selenium powder to the calcined product obtained in S2 is 5:1) are calcined at 550°C for 4 hours at a heating rate of 5°C / min to obtain the graphene-based bimetallic selenide composite material.

[0084] Figure 1 The graphene-based Ni prepared in Example 1 of the present invention 0.85 From the XRD diagram of Se / CoSe material, it can be seen that its phases are composed of Ni 0.85 Se and CoSe.

[0085] Figure 2 This is the SEM image of the porous graphene-based double transition metal selenide heterojunction composite material obtained in Example 1. It can be seen that most of the graphene holes are adjacent to the Ni 0.85Se / CoSe particles, particle size 100-200nm, pore size 50-100nm.

[0086] Figure 3 The graphene-based Ni prepared in Example 1 of the present invention 0.85 TEM image of Se / CoSe material shows that Ni 0.85 Se / CoSe to Ni 0.85 Heterojunction composed of Se and CoSe. Figure 3 a is a high-resolution TEM image, and it can be seen that they belong to Ni 0.85 Lattice fringes of Se and CoSe. Figure 3 b is the selected area electron diffraction pattern, it can be seen that Ni 0.85 Characteristic crystal diffraction rings of Se and CoSe.

[0087] After testing, the graphene-based bimetallic selenide composite material obtained in Comparative Example 2 has uneven selenide particle morphology and particle size, a small number of pores, and a small pore size, which is not conducive to short-distance cross-layer transport of sodium ions.

[0088] Figure 4 This is the SEM image of the graphene-based bimetallic selenide composite material obtained in Comparative Example 3 of the present invention. It can be seen that the selenide particles and pores are unevenly distributed, and there are fewer selenide particles close to the pores, which is not conducive to structural stability and short-distance rapid diffusion of sodium ions during charging and discharging.

[0089] Figure 5 This is the SEM image of the graphene-based bimetallic selenide composite material obtained in Comparative Example 4 of the present invention. It can be seen that the particle size of the selenide is uneven and the pores are not obvious, which is not conducive to the rapid cross-layer diffusion of sodium ions.

[0090] Taking the composite porous graphene-based bimetallic selenide composite material obtained in Example 1 as an example, a half-cell is assembled using the negative electrode material prepared in Example 1. The specific steps include:

[0091] 1) The active material (porous graphene-based double transition metal selenide heterojunction composite material) is mixed with conductive carbon black and binder polyvinylidene fluoride in a mass ratio of 7:2:1 in N-methyl-2-pyrrolidone, and the uniformly mixed slurry is applied on the current collector copper foil; after drying in a vacuum drying oven, it is cut into circular electrode sheets;

[0092] 2) The prepared electrode sheet was used as the negative electrode, metallic sodium was used as the counter electrode, and the glass fiber diaphragm (GF / D) was used as the diaphragm; the electrolyte used was NP-035 electrolyte (NaPF 4 Dissolved in (1 mol·L -1 )ethylene glycol dimethyl ether (DME); LIR2035 type battery shell is used to assemble a button type sodium ion battery.

[0093] Figure 6 The comparison of the rate performance of the battery assembled by the materials prepared in Example 1 of the present invention and Comparative Example 1 shows that the rate performance of the battery assembled by the materials prepared in Example 1 of the present invention and Comparative Example 1 is as follows: -1 At the current density, the rate capacity of Example 1 is higher than that of Comparative Example 1.

[0094] Figure 7 The batteries assembled with the materials prepared in Example 1 and Comparative Example 1 of the present invention were respectively -1 The results show that after 1000 cycles, the capacity of Example 1 (457.9 mAh g -1 ) is higher than the capacity of comparative example 1 (409.1 mAh g -1 ).

[0095] For those skilled in the art, it is easy to improve and modify the present invention without departing from the technology of the present invention, and these improvements and modifications also fall within the scope of protection of the present invention. The present invention is not limited to the above-mentioned embodiments, and any changes within the claims of the present invention are covered within the scope of protection.

Claims

1. A porous graphene-based double transition metal selenide heterojunction composite material, characterized in that: It includes a porous graphene matrix and Ni 0.85 Se / CoSe polygonal nanoparticles.

2. The porous graphene-based double transition metal selenide heterojunction composite material according to claim 1, characterized in that: The pore diameter of the porous graphene matrix is ​​50-100 nm.

3. The porous graphene-based double transition metal selenide heterojunction composite material according to claim 1, characterized in that: The Ni 0.85 The particle size of Se / CoSe polygonal nanoparticles is 100-200 nm.

4. The method for preparing the porous graphene-based double transition metal selenide heterojunction composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Dissolve a cobalt source and a nickel source in water to obtain a metal salt solution; subject the graphene source solution to ultrasonic treatment to obtain a graphene solution; drop the metal salt solution into the graphene solution, stir, add ammonia water, oil bath, and freeze-dry to obtain a metal-graphene precursor; S2, calcining the obtained metal-graphene precursor to obtain metal-graphene; S3, selenizing the obtained metal-graphene with a selenium source to obtain the porous graphene-based double transition metal selenide heterojunction composite material.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the cobalt source to the nickel source is 1 to 2:

2.

6. The preparation method according to claim 4, characterized in that: In S1, the mass ratio of the introduced cobalt source to the graphene source is 2:1-3.

7. The preparation method according to claim 4, characterized in that: In S3, the mass ratio of the introduced selenium source to the metal-graphene is 5 to 3:

1.

8. The preparation method according to claim 4, characterized in that: The stirring time in S1 is 12 to 24 hours; the oil bath temperature is 60 to 80° C., and the stirring time is 4 to 6 hours.

9. The preparation method according to claim 4, characterized in that: The calcination temperature is 700-900° C., and the time is 1-3 hours; the selenization temperature is 500-700° C., and the time is 1-3 hours.

10. An electrode sheet slurry prepared using a porous graphene-based double transition metal selenide heterojunction composite material, characterized in that: The raw materials are a porous graphene-based double transition metal selenide heterojunction composite material, conductive carbon and a binder, wherein the mass ratio of the porous graphene-based double transition metal selenide heterojunction composite material, the conductive carbon and the binder is 5 to 8:1 to 3:1.

Citation Information

Patent Citations

  • Preparation method and application of heterostructure yolk shell type double-transition metal selenide composite material

    CN116387481A

  • Preparation method and application of porous graphene loaded selenium-cobalt-iron nanoparticle composite material

    CN116525794A